PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI UPT. PSDA KUALUH BARUMUN DINAS PSDA PROVINSI SUMATERA UTARA - Arasy Ayu Setiamy (Jurnal Ilmu Manajemen METHONOMIX, 2018)
Motivation is often interpreted as an impulse. Encouragement or energy is the movement of the soul and body to do. So the motive is a driving force that moves humans to behave, and in their actions, it has a certain purpose. While discipline is also very closely related to employee productivity because in departments, especially civil servants, there are also laws that emphasize discipline, which is sometimes violated by employees. This study will analyze the influence of motivation and work discipline on work productivity in the North Sumatra Province PSDA Service. The result of this study is that motivation and work discipline has a significant effect on employee work productivity.